Konseling ibu hamil dan penggunaan kontrasepsi pasca persalinan - Dian Herawati; Siswanto Agus Wilopo; Mohammad Hakimi (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Influence of family planning counseling using decision-making tool in pregnant women on postpartum contraception use: randomized controlled trialsPurpose: Analyzed the influence of family planning counseling using the Decision-Making Tool (DMT) on postpartum contraceptive use. Methods: An experimental study with randomized controlled trials design. The study population was pregnant women during their pregnancy at public health center in Yogyakarta. Samples were obtained randomly which meet the inclusion and exclusion criteria. The independent variable was the family planning counseling interventions using DMT. The dependent variable was the postpartum contraceptive use. Bivariable analysis used chi-square test with significance of p-value of <0.05 and multivariable analysis used logistic regression. Results: The proportion of postpartum contraceptive use was greater in the intervention group than the control group with a percentage difference of 61%. Counseling used DMT in pregnant women had a significant influence on postpartum contraceptive use (p <0.05) whereas age, parity, education, spousal communication and information exposure showed no significant effect on postpartum contraceptive use. Conclusions: Decision-Making Tool of family planning was effective giving influence on postpartum contraceptive use.